Impact of the COVID-19 pandemic on the presentation of surgical conditions. Experience of Hospital de Clínicas in Uruguay - Guarneri, Carolina S.; Folonier, Juan C.; Machado, Fernando (Revista Argentina de Cirugía, 2021)
Background: COVID-19 was declared a global health emergency by WHO on March 11, 2020. As a result of the pandemic, patients’ visits to the emergency department have been affected and are reflected in the presence of complications associated with the course of the disease. Objectives: To evaluate the stage of the conditions requiring emergency surgery at the moment of consultation in the context of the pandemic. To analyze postoperative morbidity and mortality. To analyze if there were changes in the selection of the surgical approach. Material and methods: We conducted a single-center, retrospective and observational cohort study at the university center Hospital de Clínicas. Two study groups were generated to compare two populations over the same time interval (from March 13 to December 13), but differentiated by the presence of the COVID-19 pandemic and its influence. Results: The cohort was made up of 765 patients, 371 in group A and 394 in Group B. The presence of complications associated with the course of the disease and postoperative morbidity and mortality was higher in the group influenced by the pandemic (p = 0.0001 and p = 0.001, respectively). The laparoscopic approach was more common in group B (p =0.006). Conclusions: In general, the percentage of emergency surgical conditions in Hospital de Clínicas of Uruguay was similar in both periods. The presence of complications associated with the course of the disease and postoperative morbidity and mortality was higher in the group influenced by the pandemic, as expected due to delays in consultations.